2023
DOI: 10.3390/ijms24108528
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection of Andrographolide against Neurotoxin MPP+-Induced Apoptosis in SH-SY5Y Cells via Activating Mitophagy, Autophagy, and Antioxidant Activities

Abstract: Parkinson’s disease (PD) is associated with dopaminergic neuron loss and alpha-synuclein aggregation caused by ROS overproduction, leading to mitochondrial dysfunction and autophagy impairment. Recently, andrographolide (Andro) has been extensively studied for various pharmacological properties, such as anti-diabetic, anti-cancer, anti-inflammatory, and anti-atherosclerosis. However, its potential neuroprotective effects on neurotoxin MPP+-induced SH-SY5Y cells, a cellular PD model, remain uninvestigated. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…In their study, Prachayaporn Prasertsuksri and colleagues [17] have shown that andrographolide (andro) has significant neuroprotective effects against 1-methyl-4phenylpyridinium (MPP+), a neurotoxin that can cause loss of dopaminergic neurons, in SH-SY5Y cells. Andro reduces cell death by increasing mitophagy and autophagic clearance of alpha-synuclein and by increasing the antioxidant capacity.…”
mentioning
confidence: 99%
“…In their study, Prachayaporn Prasertsuksri and colleagues [17] have shown that andrographolide (andro) has significant neuroprotective effects against 1-methyl-4phenylpyridinium (MPP+), a neurotoxin that can cause loss of dopaminergic neurons, in SH-SY5Y cells. Andro reduces cell death by increasing mitophagy and autophagic clearance of alpha-synuclein and by increasing the antioxidant capacity.…”
mentioning
confidence: 99%